2014
DOI: 10.1111/ppl.12177
|View full text |Cite
|
Sign up to set email alerts
|

NADH-dependent glutamate synthase plays a crucial role in assimilating ammonium in the Arabidopsis root

Abstract: Plant roots under nitrogen deficient conditions with access to both ammonium and nitrate ions, will take up ammonium first. This preference for ammonium rather than nitrate emphasizes the importance of ammonium assimilation machinery in roots. Glutamine synthetase (GS) and glutamate synthase (GOGAT) catalyze the conversion of ammonium and 2-oxoglutarate to glutamine and glutamate. Higher plants have two GOGAT species, ferredoxin-dependent glutamate synthase (Fd-GOGAT) and nicotinamide adenine dinucleotide (NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 43 publications
(61 reference statements)
1
66
0
Order By: Relevance
“…Furthermore, NH 4 + assimilation-related enzyme expressions were analyzed. In Arabidopsis roots, GS/GOGAT genes have been reported to be induced following NH 4 + re-supply (Konishi et al 2014), and the six genes shown in Fig. 4 that encode GS or GOGAT are differentially expressed in bes1-D compared to En2 (Yu et al 2011).…”
Section: Fig 5 Gs Activity In the Shoots And Seminal Roots Of 13-d-oldmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, NH 4 + assimilation-related enzyme expressions were analyzed. In Arabidopsis roots, GS/GOGAT genes have been reported to be induced following NH 4 + re-supply (Konishi et al 2014), and the six genes shown in Fig. 4 that encode GS or GOGAT are differentially expressed in bes1-D compared to En2 (Yu et al 2011).…”
Section: Fig 5 Gs Activity In the Shoots And Seminal Roots Of 13-d-oldmentioning
confidence: 97%
“…Furthermore, the regulatory mechanism underlying this activity has been determined to involve NH 4 + assimilation products, rather than NH 4 + itself being responsible for AMT expression (Rawat et al 1999). In Arabidopsis roots, GS/GOGAT genes, encoding glutamine synthetase and glutamine oxoglutarate aminotransferase, also known as glutamate synthase, are upregulated following re-supply of NH 4 + (Konishi et al 2014). Phytohormones play important roles in NH 4 + -related plant growth and stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate altered patterns in photorespiration in mutants lacking NADP-MDH 12 . Since Fd-GOGATs play an important role in photorespiratory ammonium assimilation, 15 the expression pattern of both Fd-GOGAT isoforms was analyzed in nadp-mdh knockout plants (Fig. 2).…”
mentioning
confidence: 96%
“…1). While the NADH-GOGAT is crucial for ammonium assimilation in roots, 15 Fd-GOGATs contribute to the assimilation of ammonium derived from photorespiration which doesn’t seem to be influenced in line 159.…”
mentioning
confidence: 99%
See 1 more Smart Citation